Opponent or allied? An European analysis of the union presence and human resource practices - Martínez-Corts, Inés; Moreno-Beltrán, Juan Pablo; Renedo, Santiago; Medina, Francisco J. (Frontiers in Psychology, 2022)
Human Resources Practices (HRPs) and unions coexist in some organizations to manage the employment relationships of the workers. In this study we analyse how the presence/absence of unions and HRPs are combined in private European organizations, and which of these combinations are related to higher levels of well-being and the quality of labour relations. Data come from 24,503 workers of private organizations, obtained from the Sixth European Working Conditions Survey. Latent profiles analysis and different analyses of the variance suggested four different profiles. The profile with the greatest presence of HRPs and Union presence is related to the highest levels of employees’ well-being and quality of labour relations in organizations, whereas those organizations with a low level of union presence or HRPs reached the worst levels in employees’ well-being and quality of labour relations indicators. The results and their practical implications are discussed.